Press Nationalism: A Case Study of the Role of Medan Prijaji In Growing National Awareness - RM Joko Prawoto Mulyadi (The International Journal of Politics and Sociology Research, 2021)
As an interesting study theme, nationalism or other terms related to it also have their own uniqueness and complexity. This is because nationalism is often written with a capital letter 'N'. That is, it is already associated as an ideology as well as other ideologies such as Marxism, Socialism, and so on. However, what I will discuss in this work is not Nationalism with 'N', but nationalism with 'n'. At first glance, what is the meaning of a capital letter or not, but later in the discussion it will have a big impact. What is meant by nationalism by 'n' is not as an ideology, but a sense of nationality. Or in other terms it is also called national consciousness. This model of nationalism will be our discussion. A national consciousness sown in the dry fields of the colony called the Dutch East Indies. Not farmers or cultivators, but journalists who sow the seeds of national awareness through the media in the form of newspapers. In this case, the newspaper in question is, of course, the newspaper that initiated the effort to foster national awareness. and the choice fell on a newspaper published in 1907, Medan Prijaji, with a journalist with a strong character, RM Tirto Adhi Soerjo. This newspaper was chosen because apart from being a pioneer in the effort to raise awareness of 'us' as a nation, he also has a firm political stance. From jargon to articles, this newspaper, which had a circulation of 2000, really drew a firm line between 'us' and 'you'.